Land acquisition for industrial development and its repercussions on the peace of the local farming communities in Lume District, Oromia, Ethiopia - Fikadu Belda; Gutema Imana; Abebe Lemessa; Zerihun Doda (Cogent Social Sciences, 2024)
AbstractThis study sought to shed light on the repercussions of land acquisition process for the development of industries on the peace of farming communities. A case study design and primary and secondary data sources were used for this study. Data were collected through in-depth interviews, key informant interviews, focus group discussions, and document analysis. Qualitative data were then coded, thematized, and analyzed using a thematic analysis approach. The findings of the study indicated that the administrative bodies used unjust, coercive, and violent practices such as deceiving, confusing, cheating, labeling, defaming, intimidating, assaulting, and imprisoning farmers to appropriate their land without their will. These practices were characterized by non-manifested conflict that was signaled by partiality and corruption, non-violent conflict that was signaled by the use of power, and violent conflict that was signaled by the use of violence. Besides disrupting the overall peace of the farming communities, a flawed land acquisition process resulted in violent conflict at different times and is a potential threat to peace in the study area. Accordingly, developing inclusive and participatory policies, ensuring smallholder participation, implanting committed, loyal, and effective leadership, as well as addressing engrained land acquisition-related resentment, are crucial recommendations.